2018
DOI: 10.1177/0333102418783294
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for outcome of microvascular decompression in trigeminal neuralgia: A prospective systematic study using independent assessors

Abstract: Introduction There is a lack of high-quality prospective, systematic studies using independent assessors of outcome of microvascular decompression as treatment for trigeminal neuralgia. Methods Clinical characteristics and outcome data were recorded prospectively from consecutive classical trigeminal neuralgia patients, using standardized interviews. Degree of neurovascular contact was evaluated by a 3.0 Tesla MRI blinded to symptomatic side. Patients were assessed before and 12 months after surgery by a neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 46 publications
6
33
0
1
Order By: Relevance
“…MVD is the primary option and carry a low risk of requiring a secondary procedure and facial numbness after surgery (13,14). A recent prospective study investigating the outcomes of MVD in patients with TN has found that male gender and NVC with morphological changes on preoperative MRI images, where distortion, dislocation, and distension were observed, predicted the excellent outcomes (15). This study and earlier studies have reported that the severity degree of NVC was signi cantly associated with surgical outcomes (16,17).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…MVD is the primary option and carry a low risk of requiring a secondary procedure and facial numbness after surgery (13,14). A recent prospective study investigating the outcomes of MVD in patients with TN has found that male gender and NVC with morphological changes on preoperative MRI images, where distortion, dislocation, and distension were observed, predicted the excellent outcomes (15). This study and earlier studies have reported that the severity degree of NVC was signi cantly associated with surgical outcomes (16,17).…”
Section: Discussionsupporting
confidence: 52%
“…The underlying mechanism may due to the fact that the demyelinated trigeminal nerve root remyelinates after MVD and the neuroedema at the symptomatic NVC were released (3,18). Therefore, the preoperative neurological imaging assessment of NVC severity is important in predicting patients' outcomes beyond diagnosis (15,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NVC causing atrophy or displacement of the nerve (or both) was highly associated with pain on the symptomatic side of patients with classic TN in contrast to NVC in general, according to this study 17 . A more recent study reported that neurovascular contact with morphological changes to the nerve as detected by 3-Tesla MRI and male gender was associated with better outcome following microvascular decompression surgery 18 . Excellent outcome and concomitant persistent pain, current age, or disease duration were not correlated 18 .…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…In a recent prospective study using independent assessors of outcome, it was demonstrated that patients with classical TN have a higher chance of a successful outcome after microvascular decompression (MVD) compared to idiopathic TN patients . However, a significant proportion of patients with idiopathic TN also had good pain relief after MVD . Thus, it seems that an NVC without morphological changes does play a role in some idiopathic TN patients who are therefore not truly ‘idiopathic'.…”
Section: Section 1: Diagnosismentioning
confidence: 99%